(untitled) (Research, Society and Development, 2021)
Introduction: Aging has been increasing over the last decades, thus increasing the risk of cognitive decline, functional decrease and worsening of quality of life. The practice of physical exercise gains prominence for its preventive and/or therapeutic character, of low and affordable cost. Most studies use long periods of intervention (6 months or more), with aerobic or resistance exercises, however there are few studies that use the circuit training methodology. The present study evaluated the effects of 12 weeks of a circuit training program on functional aspects, cognitive functions and quality of life of the elderly. Methodology: Twenty elderly were submitted to a circuit training program for a period of 12 weeks and evaluated in the pre- and post-intervention period. The following were used: SF-36 questionnaire, Mini Mental State Examination (MMSE), Time Get up and go (TUG), Stand Lift Test, Forearm Flexion Test, 6-minute Gait Speed Test. Results: The data obtained showed a 26% improvement in the mean of the SF-36, 7% in the gait speed for the 6-minute test, and an increase of 1.6 points for the mini mental. Conclusion: Physical training in circuit was able to improve quality of life, functionality and cognition in the elderly.